Retracted: Adoption of Magnetic Resonance Image Features under Segmentation Algorithm in Effect Evaluation of Ginkgo Diterpenoid Lactone Glucamine Injection in Treatment of Cerebral Infarction - Imaging, Contrast Media & Molecular (Contrast media and molecular imaging, 2023)
[This retracts the article DOI: 10.1155/2022/4558702.].[This retracts the article DOI: 10.1155/2022/4558702.].